Ecological and Specific Evidence-Based Safe Return To Play After Anterior Cruciate Ligament Reconstruction In Soccer Players: A New International Paradigm - Florian Forelli; Nicolas Le Coroller; Maxime Gaspar; Geoffrey Memain; Georgios Kakavas; Nicholas Miraglia; Patrice Marine; Pascal Maille; Timothy E Hewett; Alexandre JM Rambaud (International Journal of Sports Physical Therapy)
Existing return to play (RTP) assessments have not demonstrated the ability to decrease risk of subsequent anterior cruciate ligament (ACL) injury after reconstruction (ACLR). RTP criteria are standardized and do not simulate the physical and cognitive activity required by the practice of sport. Most RTP criteria do not include an ecological approach. There are scientific algorithms as the "5 factor maximum model" that can identify risk profiles and help reduce the risk of a second anterior cruciate ligament injury. Nevertheless, these algorithms remain too standardized and do not include the situations experienced in games by soccer players. This is why it is important to integrate ecological situations specific to the environment of soccer players in order to evaluate players under conditions closest to their sporting activity, especially with high cognitive load. One should identify high risk players under two conditions: Clinical analyses commonly include assessments such as isokinetic testing, functional tests (hop tests, vertical force-velocity, profile), running, clinical assessments (range of motion and graft laxity), proprioception and balance (Star Excursion Balance Test modified, Y-Balance, stabilometry) and psychological parameters (kinesophobia, quality of life and fear of re-injury). Field testing usually includes game simulation, evaluation under dual-task conditions, fatigue and workload analysis, deceleration, timed-agility-test and horizontal force-velocity profiles. Although it seems important to evaluate strength, psychological variables and aerobic and anaerobic capacities, evaluation of neuromotor control in standard and ecological situations may be helpful for reducing the risk of injury after ACLR. This proposal for RTP testing after ACLR is supported by the scientific literature and attempts to approximate the physical and cognitive loads during a soccer match. Future scientific investigation will be required to demonstrate the validity of this approach.